Analisis Arsitektural Istana Buckingham sebagai Setting Film “The Young Victoria” - Peminoverman Tafonao; Dara Wisdianti (Jurnal Teknik dan Teknologi Indonesia, 2024)
This research analyzes the use of Buckingham Palace as a filming location for The Young Victoria using Greimas' semiotic narrative approach and Freud's psychoanalysis. The film represents Queen Victoria's life journey from childhood to her coronation as Queen of England, with a strong narrative point of view. Through semiotic methods, this study explores the relationships between characters in the film and how the role of palace architecture supports the visual narrative and symbolism of monarchical power. In addition, this study explores the historical and architectural value of Buckingham Palace, including design changes over time and their relevance in supporting the atmosphere of a movie set in history. The method used is descriptive qualitative with data sources coming from literature, documentation, and online media interviews. The results show that the presence of historical architecture not only enriches the aesthetics of the movie, but also strengthens the narrative meaning.